2021
DOI: 10.1136/bmjopen-2020-045961
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture-related adverse events: systematic review and meta-analyses of prospective clinical studies

Abstract: ObjectiveOverview on risks of acupuncture-related adverse events (AEs).DesignSystematic review and meta-analyses of prospective studies.Data sourcesPubMed, Scopus and Embase from inception date to 15 September 2019.Eligibility criteria for selecting studiesProspective studies assessing AEs caused by needle acupuncture in humans as primary outcome published in English or German.Data extraction and synthesisTwo independent researchers selected articles, extracted the data and assessed study quality. Overall risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 61 publications
0
23
1
2
Order By: Relevance
“…1). 1‐134 Of those, 65 of 94 publications (69.1%) were included in the qualitative analysis because they reported at least 1 type of AE,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). 1‐134 Of those, 65 of 94 publications (69.1%) were included in the qualitative analysis because they reported at least 1 type of AE,…”
Section: Resultsmentioning
confidence: 99%
“…In a current meta-analysis by Baumler et al of different patient populations, the authors found that an AE can be expected in every 10th patient or at every 13th acupuncture treatment. 15 Most of the AEs were minor and transient or even intended effects, indicating a favorable physiological response. Serious AEs were very rare.…”
Section: Table 3 Continuedmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the exact mechanism of acupuncture is difficult to research and not yet completely understood, clinical trials have shown good evidence of acupuncture efficacy in the treatment of HD and for the prevention of migraine, TTH, or chronic HD [ 224 ]. As adverse events are mild and serious adverse events are rare, acupuncture can be considered a safe treatment [ 225 ].…”
Section: Discussionmentioning
confidence: 99%